Perfusion imaging of the right perisylvian neural network in acute spatial neglect - Zopf, Regine; Fruhmann Berger, Monika; Klose, Uwe; Karnath, Hans-Otto (Frontiers in Human Neuroscience, 2009)
Recent studies have suggested a tightly connected perisylvian neural network associated with spatial neglect. Here we investigated whether structural damage in one part of the network typically is accompanied with functional damage in other, structurally intact areas of this network. By combining normalized fluid-attenuated inversion-recovery (FLAIR) imaging, diffusion-weighted imaging (DWI), and perfusion-weighted imaging (PWI) we asked whether or not lesions centering on fronto-temporal regions co-occur with abnormal perfusion in structurally intact parietal cortex. We found small areas of perfusion differences in the superior temporal gyrus (STG), inferior frontal gyrus (IFG), insula, and postcentral gyrus of our patients with spatial neglect. However, with thresholds applied to delineate behaviorally relevant malperfusion of brain tissue, the analysis of normalised time-to-peak (TTP) and maximal signal reduction (MSR) perfusion maps did not reveal significant changes outside the area of structural damage. In particular, we found no abnormal perfusion in the structurally intact inferior parietal lobule (IPL) and/or the temporo-parietal junction (TPJ). The present results obtained in three consecutively admitted neglect patients indicate that structural damage in one part of the right perisylvian network associated with spatial neglect does not necessarily require dysfunction by malperfusion in other, structurally intact parts of the network to provoke spatial neglect. The neural tissue in the fronto-temporal cortex appears to have an original role in processes of spatial orienting and exploration.